Polish adaptation and validation of the Freiburg Mindfulness Inventory - Radoń, Stanisław (Studia Psychologica: Theoria et praxis, 2017)
In this research study the polish 14-item version of Freiburg Mindfulness Inventory (FIU-14; Wallach, Buchheld, Buttenmüller, Kleinknecht, Schmidt, 2006) based on strong results of empirical research of mindfulness was developed and validated. The psychometric properties of the Polish version were assessed in a sample of 578 peoples (128 artistic gifted young peoples 15–19 y.o. and 450 adults 20–50 y.o.). Construct validity was examined with reliability analysis, confirmatory factor analyses and by relating the FIU-14 to others measures of psychological traits (neuroticism, emotional stability, integration, rumination, openness to experience, extraversion, reflection, personality disorders). The results confirmed reliability(α = 0,75), stability (r = 0,91) and validity of FIU-14 (1-factor model of mindfulness: CMIN/df = 1,50; GFI = 0,95; AGFI = 0,93; CFI = 0,93; RMSEA = 0,04; PCLOSE = 0,81) for nonclinical population aged 20–50. Conditional use of abbreviated version of the questionnaire (FIU-8) is permitted   r persons aged 15–19 (two-factor model). Replications in meditating samples and in patients are needed.